Implementation of Play Methods in Developing Concentration Skills in Children at TKIP Ummul Mukminin - Yulianti, Annisa; Permanik, Intan; Komala, Vivi Patra (Journal of Islamic Early Childhood Education (JOIECE): PIAUD-Ku, 2025)
Early childhood is a crucial stage for children's growth and development. Through play, various aspects cognitive, social-emotional, physical-motor, language, moral, and spiritual develop significantly. Appropriate stimulation and attention can positively influence these developments. This study aims to explore the implementation of play-based methods to improve children's learning concentration at TKIP Ummul Mukminin, Katapang District, Bandung Regency. Employing a qualitative approach, data were collected through interviews and direct field observations. The research focuses on how the play method is applied, along with its strengths and limitations in enhancing concentration. The findings reveal that children's concentration levels vary according to individual characteristics. However, after implementing the play method, most children showed improved concentration during learning activities. The establishment of classroom agreements and rules also contributed to a more conducive learning environment. Strengths observed include increased curiosity and enthusiasm, leading to optimal learning outcomes. On the other hand, challenges remain, such as classroom layout issues (minimal partitions causing distractions) and inconsistent parental discipline at home, which hinders the reinforcement of structured behavior in school